Effect of maize silage supplementation to grass silage harvested at different maturity stages on ad libitum intake - Marina Vranić; Mladen Knežević; Goran Perčulija; Ivana Matić; Damir Turčin (Mljekarstvo)
The objective of the investigation was to determine ad libitum intake of fresh ration, dry matter (DM) and the organic matter (OM) of grass silage from the primary growth harvested at different maturity stages in interaction with maize silage (33 % and 67 %, DM based) in g kg-1 of the metabolic body weight (M0.75). Grass silage was harvested in three maturity stages of orchardgrass (Dactylis glomerata L.) that was dominant grass in the sward (late vegetative, internode elongation, flowering). The study consisted of ten feeding treatments with 10 whether Charolais sheep in incomplete changeover design. Dry matter content of I, II and III cutting term was 396, 408 i 463 g kg-1 of the fresh sample, respectively, while crude protein (CP) content was 119.6, 98.0 and 93.0 g kg-1 of DM respectively. Dry mater and starch concentration in maize silage was 264 g kg-1 of fresh sample and 211 g kg-1 of DM respectively. Inclusion of 67 % of maize silage in the grass silage of the and grass silage of the II cutting term based ration significantely increased (P<0.05) fresh ration ad libitum intake, while with the III cutting term of grass silage both levels of the maize silage (33 % vs. 67 %) significantely increased (P<0.05) fresh ration ad libitum intake. Inclusion of maize silage to grass silage of the I, II or III cutting term based ration (33 % vs. 67 %) did not have a significant influence on DM or OM ad libitum intake. It was concluded that a positive response of maize silage inclusion in the grass silage based diet is dependent on the quality of both, the maize silage (DM and starch concentration) and the grass silage (maturity stage at harvesting). The maize silage was probably of lower quailty then required for improved ad libitum DM and OM intake of the grass silage based ration.